2020
DOI: 10.2174/1871526519666190617162701
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Pathophysiological Targets of Psoriasis for Future Therapeutic Strategies

Abstract: Psoriasis is a chronic autoimmune skin disorder which involves complex interactions between genes, keratinocytes, T-cells and inflammatory cells it is affecting 2-3% population worldwide. Molecular biology and cellular immunology of psoriasis, when linked with biotechnology and genetic studies can help to understand the pathophysiology of psoriasis. T-cells activation, keratinocyte hyperproliferation and angiogenesis are the core mechanisms entailed in the development of psoriasis lesion. Investigators are try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The major biological pathways of psoriasis were deduced by a literature survey (Rácz and Prens, 2009 ; Bejarano and Valdecantos, 2013 ; Baliwag et al, 2015 ; Hugh and Weinberg, 2018 ; Yadav et al, 2019 ), and this revealed that Tumor necrosis factor-α (TNF-α), interleukin-1α (IL-1α), IL-1β, IL-13, IL-12/23, IL-17, IL-22, IL-36γ, Interferon-γ (IFN-γ), Nuclear Factor-κB (NF-κB), endothelial nitric oxide synthase (eNOS), inducible NOS (iNOS), Peroxisome proliferator-activated receptor gamma (PPAR-γ), MAP Kinase-Activated Protein Kinase 2 (MAPK2), Janus Kinase 1 (JAK1), JAK2, JAK3, and the Signal transducer and activator of transcription 3 (STAT3) play important roles in the pathogenesis of psoriasis. Moreover, the druggable macromolecules were also confirmed by Kyoto Encyclopedia of Genes and Genomes (KEGG) database ( https://www.kegg.jp/ ), which showed that the NF-κB, IL-17, and IL-36 pathways are particularly involved in psoriasis (KEGG ID: H01656).…”
Section: Methodsmentioning
confidence: 99%
“…The major biological pathways of psoriasis were deduced by a literature survey (Rácz and Prens, 2009 ; Bejarano and Valdecantos, 2013 ; Baliwag et al, 2015 ; Hugh and Weinberg, 2018 ; Yadav et al, 2019 ), and this revealed that Tumor necrosis factor-α (TNF-α), interleukin-1α (IL-1α), IL-1β, IL-13, IL-12/23, IL-17, IL-22, IL-36γ, Interferon-γ (IFN-γ), Nuclear Factor-κB (NF-κB), endothelial nitric oxide synthase (eNOS), inducible NOS (iNOS), Peroxisome proliferator-activated receptor gamma (PPAR-γ), MAP Kinase-Activated Protein Kinase 2 (MAPK2), Janus Kinase 1 (JAK1), JAK2, JAK3, and the Signal transducer and activator of transcription 3 (STAT3) play important roles in the pathogenesis of psoriasis. Moreover, the druggable macromolecules were also confirmed by Kyoto Encyclopedia of Genes and Genomes (KEGG) database ( https://www.kegg.jp/ ), which showed that the NF-κB, IL-17, and IL-36 pathways are particularly involved in psoriasis (KEGG ID: H01656).…”
Section: Methodsmentioning
confidence: 99%